Development of a canine epidermis equivalent model for evaluation of sensitization - Marques, M (2022)
Background Canine atopic dermatitis (cAD) is a genetic-predisposed allergic and pruritic inflammatory skin condition, associated with sensitization to environmental allergens. Keratinocytes can produce several inflammatory mediators, in response to several other host mediators, antigens, and pathogens by virtue of their wide range of surface receptors, some of them dysregulated in cAD individuals. A histotypical cell cultured-derived tissue may be used to replace animal testing and are imperative to avoid armful, drawn-out tests to assess chemicals for their capacity to disrupt skin or cause sensitization. The aim of our study was to develop a histotypical canine epidermis equivalent, that could be used for the assessment of skin irritation and sensitization, useful in studies of cAD pathogeny and pharmacology. Methods Canine keratinocytes progenitor cells were seeded in air-lift culture, using an adapted version of the CELLnTECTM protocol. Irritation and sensitization protocols were adapted from human equivalent validated tests. For histological analysis, samples fixed in neutral-buffered formalin and paraffin sections were routinely processed for biopsies and stained with hematoxylin and eosin. Results A multilayer (3-4 cell-layer thick) of canine keratinocytes was developed in air-lift culture, originating a stratified epidermal-like tissue, confirmed by histological analysis. This epidermal-like tissue exhibited functional characteristics of the normal epidermis, showing an adequate impermeabilization after 0.1% Triton X-100 exposure for 4h. Additionally, the epidermis model responded adequately to the positive [5% SDS, 20% salicylic acid in AOO (acetone and olive oil 4:1)] and negative (PBS and AOO) controls of the irritation and sensitization tests, assessed by the quantification of cellular viability and of the secreted IL-18. Conclusion As predicted, a canine epidermis analog was developed. This is a promising canine epidermis model that can be used for the study of skin-derived cAD triggering factors, and in the development and evaluation of new drugs for topical applications. Acknowledgements: Project co-financed by the European Union Fund – Portugal 2020, Alentejo 2020 – Ref. 03/SI/2017 (ALT20-03-247-FEDER-033578).